A domain-decomposition generalized finite difference method for stress analysis in three-dimensional composite materials. (June 2020) - Wang, Yuanyuan; Gu, Yan; Liu, Jianlin
Abstract: In this paper, a new framework for stress analysis of three-dimensional (3D) composite (multi-layered) elastic materials is presented. In our computations, the composite material is firstly decomposed into several sub-domains by using the domain-decomposition technique, and then in each of the sub-domain, the stresses are approximated by using a meshless generalized finite difference method (GFDM). Along the sub-domain interfaces, compatibility of displacements and equilibrium of tractions are imposed. The new method yields a sparse and banded matrix system which makes it very attractive for large-scale engineering simulations. Numerical examples with up to 500, 000 unknowns are solved successfully using the developed GFDM code.